Perancangan Desain Aplikasi Pelatihan Karyawan PT. Darya-Varia Laboatoria Tbk. Gunung Putri Plant (Current Research in Education: Conference Series Journal, 2023)
The increasingly massive use of technology makes computers the main requirement for data management, but in contrast to PT Darya-Varia Laboratoria Tbk which still uses paper in training attendance, after employees are absent through paper, the data will be processed with Microsoft Excel, its use is still considered less effective because of the large number of data redundancy that occurs. The purpose of this research is to reduce data redundancy at the time of data input. The method used in this research is Design Thinking Method. So that the results of this design provide recommendations in the form of a UI/UX model on desktop-based applications. This design model is made by taking into account the problems that occur, the model recommendations are equipped with a